Relationships between stakeholders and reports using Fuzzy relations - D'onofrio, Paula (2013)
The main parameter of the concept of corporate social responsibility is to consider the expectations of different stakeholders (employees, partners, customers, local communities, the environment, shareholders, vendors, etc.) regarding the behavior of companies. Even if a relatively homogeneous group is selected, as in this paper, differences are seen when establishing preference levels. These discrepancies are inherent to individuals based on their interests, which may be affected by both concrete and subjective circumstances. This paper is divided into two parts. The first part consists in segmenting preferences of users from the agribusiness sector with respect to social and environmental accounting information. Then, based on this prior task, we will try to determine which standard reports relating to social and environmental information meet to a greater extent these users’ needs. This will be done using fuzzy incidence matrices. Through the max-min composition of matrices, a relation matrix of users and the chance of meeting their information needs according to the standard reports considered for this work is produced. This paper has sought to address the preferences of users of social and environmental information through a scientific methodology, trying to group users by means of the affinities theory. We believe this proposal may help identify similar stakeholders in the future, so as to schedule interviews, establish common patterns and be able to prepare reports meeting their needs, or, as in the case proposed, use existing reporting models.